HUBUNGAN KARAKTERISTIK IBU HAMIL DENGAN KEJADIAN ANEMIA DI PUSKESMAS HALIWEN KABUPATEN BELU - Ermelinda Moruk; Ni Ketut Somoyani; Ni Nyoman Suindri (Journal of Innovation Research and Knowledge, 2025)
Amenia can cause complications during pregnancy, childbirth and postpartum. Around 40% of maternal deaths in developing countries are related to anemia in pregnancy. This study aims to determine the relationship between the characteristics of pregnant women and the incidence of anemia at the Haliwen Community Health Center, Kakuluk Mesak District, Belu Regency. This type of research is analytical research with a Cross Sectional Study approach, where the total population taken was 378 respondents. The research variables consist of independent variables, namely maternal age, gestational age, education, employment, pregnancy spacing, and CED, as well as the dependent variable, namely the incidence of anemia in pregnant women. The research instrument uses secondary data described in the questionnaire. The research results were analyzed using SPSS 21 with the Chi Square test method to determine the relationship between variables. There is a relationship between anemia and maternal age ƿ-value = 0.005, gestational age ƿ-value = 0.002, education ƿ-value = 0.000, pregnancy interval ƿ-value = 0.017, Parity ƿ- value = 0.017, Birth ƿ-value = 0.000 and there is no relationship between anemia and work ƿ-value = 0.238. There is a relationship between anemia and maternal age, gestational age, education, spacing, parity and CED. For work, it is not enough to affect the anemia condition of pregnant women. Health programs need to prioritize nutritional education for pregnant women